Value chain analysis of peruvian avocado oil production - Quiroz , Ana María (2021)
Currently, Peru is the third-largest global exporter of Hass avocado (Trademap, 2019), known in the main markets. For this reason, this article proposes to use the value chain tool to provide information on commercialization guidelines of the most representative derivative, avocado oil. In this sense, the Peruvian avocado oil value chain was designed to propose a model based on the main existing guides, complemented by estimating the effort required to implement a model plant to extract said oil, with the final objective of proving the feasibility of avocado oil production in Peru, evaluating the key points to implement the production chain and provide competitive proposals.